Performance Analysis of Fiber Attenuation in Passive Optical Networks - Augustus E. Ibhaze; Adekunle O. Gbadebo; Akinwumi A. Amusan; Samuel N. John (IAES Indonesian Section, 2023)
The introduction of Fiber Optics cables in broadband Internet distribution has been a game changer in bulk capacity delivery, speed, reliability and penetration. However, the uncurbed incessant existence of cuts and failures have threatened the growth of Internet connectivity as a whole. In this work, the impact of fiber cuts is investigated using a hybrid approach, encompassing both real-world data from a live GPON network and simulations using OptiSystem 12 for FTTH GPON scenarios. Fiber cuts and failures are emulated by introducing varying attenuation levels in the simulated network's feeder cable section within OptiSystem 12, while in the live GPON network, the attenuation is induced by introducing wrap bends in the last-mile patch cord. The findings reveal a consistent pattern in both simulated and live data for both downstream and upstream traffic scenarios. As attenuation levels increased, there was a corresponding decline in Q-factor, Eye Height, and optical power, coupled with a concurrent rise in the minimum BER. Thus, in the most severe scenario, fiber cuts can result in service degradation and eventual service outage. To mitigate this issue, the implementation of a typeB PON protection system with a wireless auto-failover technique is proposed. Adoption and deployment of the proposed technique and deliberate maintenance measures alongside thorough supervision are suggested to be possible solutions to fiber cuts in metropolitan parlance.